Proceedings of the February, 1969, General Meeting (The Southern African Institute of Mining and Metallurgy)
The February General Meeting of the Institute was held in Kelvin House, Johannesburg, on 19th February, 1969 at 4.30 p.m. Mr R. C. J. Goode (President) was in the Chair. There were also present forty-six Members, including Messrs H. E. Cross, A. R. C. Fowler, P. Lambooy, D. G. Maxwell, Dr J. T. McIntyre, Messrs J. A. Nixon, V. C. Robinson and P. W. J. van Rensburg (Council Members), Messrs G. Abdinor, H. F. Allan, R. E. Barnes, M. M. Bayley, J. K. Boyd, R. R. M. Cousens, R. E. F. Cowley, D. Savile Davis, H. J. Davisson, C. T. Fenton, J. Fergusson, J. Fritz, M. L. Fitzgerald, J. M. Gosnell, J. C. Hall, S. A. Hancox, D. M. Jamieson, Dr D. G. Krige, Messrs J. E. V. Leeuwen, A. Louw, C. F. Louw, B. H. L. Leach, R. B. MacGillivray, C. S. McPhail, E. Margo, G. G. Nicolson, E. Pavitt, M. P. Pearse, F. O. Read, Dr M. D. G. Salamon, Dr H. S. Sichel, Messrs D. Storrar, S. G. Taussig, A. H. Taute, E. B. Viljoen and P. A. von Wielligh. Sixteen Associate Members, including Messrs S. T. Baron, W. M. Fitzpatrick, M. R. Fuller-Good, P. R. Garcia, H. G. Gericke, P. D. Hatfield, R. Hemp, G. S. Lee, Miss V. E. Marting, Messrs A. H. Munro, R. C. Power, O. F. Rheeder, G. C. Thompson and N. Zolezzi. Two Graduates, Messrs D. Bosley and J. C. Sutherland. Three Affiliates, Messrs R. K. Briggs, A. B. Cook and G. M. Thain. One Student, Mr P. W. Henrard. Twenty-three Visitors, including Messrs N. J. W. Bell, R. G. Bushell, A. Bryan, J. F. Cillie, C. M. de Beer, Dr F. H. Deist, Messrs D. S. Drake, P. G. du Plessis, R. W. Hodgson, D. M. Hawkins, S. C. H. Kearns, M. D. Labuschagne, L. Munro,R. Murchison and L. Robinson. Secretary, Mr D. C. Visser. Total present: Ninety-two. OBITUARIES The President: "It is my sad duty to announce the death of the following members of the Institute. Edward Frank Jud Bulman, Life Member, who joined the Institute in 1931 and passed away on 7th November, 1968. Elmar Fenton Chapin, Member, who joined the Institute in 1941 and passed away on 17th November, 1968. Solly Rabinowitz Rabson, Member, who joined the Institute in 1944 and passed away on 13th February, 1969. Mr. Rabson was the holder of two certificates of merit for papers presented to the Institute.